Emerging Roles of N6-Methyladenosine on HIV-1 RNA Metabolism and Viral Replication - Riquelme-Barrios, Sebastián; Pereira-Montecinos, Camila; Valiente-Echeverría, Fernando; Soto-Rifo, Ricardo (Frontiers in Microbiology, 2018)
N6-methyladenosine (m6A) is the most abundant internal modification present in Eukaryotic mRNA. The functions of this chemical modification are mediated by m6A-binding proteins (m6A readers) and regulated by methyltransferases (m6A writers) and demethylases (m6A erasers), which together are proposed to be responsible of a new layer of post-transcriptional control of gene expression. Despite the presence of m6A in a retroviral genome was reported more than 40 years ago, the recent development of sequencing-based technologies allowing the mapping of m6A in a transcriptome-wide manner made it possible to identify the topology and dynamics of m6A during replication of HIV-1 as well as other viruses. As such, three independent groups recently reported the presence of m6A along the HIV-1 genomic RNA (gRNA) and described the impact of cellular m6A writers, erasers and readers on different steps of viral RNA metabolism and replication. Interestingly, while two groups reported a positive role of m6A at different steps of viral gene expression it was also proposed that the presence of m6A within the gRNA reduces viral infectivity by inducing the early degradation of the incoming viral genome. This review summarizes the recent advances in this emerging field and discusses the relevance of m6A during HIV-1 replication.